Comparison of Peripapillary Vessel Density of Acute Nonarteritic Anterior Ischemic Optic Neuropathy and Other Optic Neuropathies With Disc Swelling Using Optical Coherence Tomography Angiography: A Pilot Study. Issue 4 (December 2021) - Chuang, Jasmine C.; Chan, Noel C. Y.; Cheung, Carol Y.; Lok, Jerry K. H.; Chan, Carmen K. M.
Abstract : Background: The purpose of this study is to quantitatively compare the peripapillary vessel density (PPVD), measured with optical coherence tomography angiography (OCT-A), between acute nonarteritic anterior ischemic optic neuropathy (NAION) and other causes of disc swelling ("others"). Methods: In this prospective comparative case series, patients with unilateral disc swelling due to acute NAION (n = 7) and "others" (n = 7) underwent OCT-A scanning of the optic nerve head with a swept-source OCT (Triton DRI-OCT), in addition to functional assessment. OCT-A images were analyzed using an automated customized MATLAB program. Comparison was made between total and 6 sectoral PPVD (radial peripapillary capillary [RPC] and choroid layers) of affected and fellow eyes; and between the 2 groups' affected eyes. Five NAION patients had repeated assessments at 1, 3, and 6 months. Results: Acute NAION eyes had a significantly lower total and superonasal PPVD (both layers) compared to fellow eyes. No such difference was observed in "others" group for the RPC layer. NAION eyes also had significantly lower total RPC PPVD than affected eyes in the "others" group. Over 6 months, NAION eyes had persistently lower RPC PPVD compared to fellow eyes but the reduced choroidal PPVD resolved by 1 month. Conclusion: The study demonstrated reduced superonasal and total RPC PPVD in acute NAION, which persisted over 6 months. Because there is currently no single diagnostic test for NAION, use of OCT-A images to analyze RPC PPVD may potentially help distinguish acute NAION from other causes of disc swelling by quantitatively demonstrating capillary dropout in the RPC layer.